A new derivative of 8-hydroxyquinoline. Features of distribution and complexation with Cu(II) and Zn(II) in two-phase systems. Issue 3 (16th April 2022) - Konshina, Dzhamilya N.; Lupanova, Ida A.; Efimenko, Sergey E.; Konshin, Valery V.
ABSTRACT: A new promising analytical reagent is proposed for the extractive recovery of Cu(II) and Zn(II). The reagent is produced upon azo coupling of 8-hydroxyquinoline with diazotized 4-(prop-2-yn-1-yloxy)aniline in yield of 54%. Its structure was confirmed by the combined data from IR, 1 Н, and 13 С NMR spectroscopy, and HRMS. The UV-VIS absorption spectra suggests an azo-hydrazone tautomerism to exist in the 2-ethoxyethanol medium and 5-(4-(prop-2-ynyloxy)phenylazo)quinolin-8-ol to be present in a chloroform or acetonitrile solution predominantly as the azo form. The extraction behavior of 5-(4-(prop-2-ynyloxy)phenylazo)quinoline-8-ol with regard to Cu(II) and Zn(II) in a chloroform–water system was studied. The stoichiometry of the extracted complex compounds and the conditional extraction constant were calculated.